(untitled) - Byron, Christopher (Hoboken, N.J., 2004)
A smarmy wallow in the sleaziest escapades of four powerful and highly visible CEOs, Byron’s latest serves up a titillating mix of snark, sanctimony and pop psychology. In his last book, the bestselling Martha, Inc., the veteran business journalist asserted that Stewart was driven by resentment toward her brutish father and her humble roots. In this new book, Byron’s analysis leads him to the loopy conclusion that his four subjects—Jack Welch, Dennis Kozlowski, Ronald Perelman and Al Dunlap—are all victims of excessive testosterone. Readers who get a chuckle out of watching rich and powerful men make fools of themselves will find plenty to like here. As for all that research: this book contains little that is especially new or valuable, unless you really care to know such details as exactly which of Welch’s uncles was a drunk
Keywords: Chief executive officers,General electric company,Giám đốc điều hành,Tổng Công ty Điện lực; Case Studies,Managment,Quản trị; United States